Consider the equation
\(9(x^{2}\ \mp\ 6x\ +\ 1)\ -\ 9x\ \times\ 4(y^{2}\ -\ 4y\ +\ 4)\ +\ 32y=119\)

\(foci\ = (h\ \pm\ ae,\ k)\)

\((1, \pm\ 5,\ 2)\)

\((6,\ 2)\ (−4,\ 2)\)

\(vertices\ = (h\ \pm\ a,\ k)\ (h\ \pm\ k,\ b)\)

\((1\ \pm\ 4,\ 2)\ (1\ \sqrt{2\ \pm,\ 3})\)

\((5,\ 2)(−3,\ 2)\ (1,\ 1)(1,\ −5)\)

\(\frac{major\ axis}{minor\ axis}=8\ +\ 6\)

\(foci\ = (h\ \pm\ ae,\ k)\)

\((1, \pm\ 5,\ 2)\)

\((6,\ 2)\ (−4,\ 2)\)

\(vertices\ = (h\ \pm\ a,\ k)\ (h\ \pm\ k,\ b)\)

\((1\ \pm\ 4,\ 2)\ (1\ \sqrt{2\ \pm,\ 3})\)

\((5,\ 2)(−3,\ 2)\ (1,\ 1)(1,\ −5)\)

\(\frac{major\ axis}{minor\ axis}=8\ +\ 6\)